SHORT REVIEW ON PAIN (VEDANA) BY SUSHRUTA - Poonam Mohod; Aaditya Bhavanbhai Shah; V.C. Deep; Sharad Mohod (International Journal of Ayurveda and Pharma Research, 2020)
Pain is an unpleasing sensation and emotional experience that links to tissue damage. It allows the body to react and prevent further tissue damage. It is an unpleasant feeling which only the individual himself can experiences because of that it cannot be objectively defined satisfactorily. However, International Association for the Study of Pain (IASP) defines pain as, “An unpleasant sensory and emotional experience associated with actual or potential tissue damage. It is not just a physical sensation, it is an influenced by attitudes, beliefs, personality and social factors, and can affect emotional and mental wellbeing” which somehow help to define pain. The present study reviewed all the literature related with pain in Ayurvedic literature as mentioned in Sushruta Samhita. The basic aim of this study was to explore briefly and review the concept of pain as per Sushruta Samhita. And for the same various books especially Sushruta Samhita and related supportive books and other web-based articles were reviewed for the better understanding of the concept. Only secondary data were used for writing this article.